The case of the wandering scholar [large type] - Saunders, Kate, 1960- (Saunders, Kate, 1960- Laetitia Rodd mystery, 2020)
It is 1851 and Mrs Rodd has received an unusual commission: wealthy businessman Jacob Welland is dying of consumption and implores our redoubtable detective to find his beloved brother, whom he has not seen for fifteen years. Joshua Welland was an Oxford scholar; brilliant, eccentric and desperately poor. Nobody can say exactly when he disappeared from his college, but he had taken to wandering the countryside and one day simply failed to return. Since then, there have been several sightings of his lonely, ragged figure. Ten years ago a friend spotted him in a gypsy camp, where it was rumoured he was learning great secrets that would one day astound the world. Mrs Rodd uses her search as an opportunity to reconnect with a couple from her past, but then a violent murder is committed and Scotland Yard are called to investigate. Mrs Rodd's old friend Inspector Blackbeard doesn't want to hear any nonsense about gypsies or secrets. Mrs Rodd, however, is convinced that something very sinister is lurking in this peaceful landscape.